A Budget of Carbonate and Terrigenous Sediments, Hanalei Bay, Kauai, Hawaiian Islands - Calhoun, R. S.; Fletcher, C. H.; Harney, J. N. (Marine Geology, 2002)
The sediment budget of Hanalei Bay on the north shore of Kauai was calculated using sedimentological and geophysical methods. The calculations of the budget subsequently allowed an interpretation of the Holocene history of the bay. The bay sediments are easily separated into marine (carbonate) and terrigenous (siliciclastic) grains. Surficial sediments are dominated by carbonate grains (∼70%) of coralline algae, coral, and mollusc fragments as well as foraminifera, Halimeda, bryozoa, and echinoderm tests. However, siliciclastic grains (e.g. olivine, plagioclase, volcanic lithics) from the Hanalei River watershed draining shield volcanic highlands are the most common individual grain type (∼27%) and form a zone of high concentration from the mouth of the Hanalei River into the center of the bay. Flooding in the bay by the post-glacial sea-level rise began soon after 11.7 kyears. The resulting marine environment caused the net deposition of 45.5±1.5×106 m3 of sediment in the bay and approximately 33.7±11.2×106 m3 of sediment on the Hanalei coastal plain. The total volume of carbonate sediment stored in the bay and coastal plain is greater than the volume likely to have been produced exclusively within the bay during the same time. Calculations indicate that approximately 2490 m3 year−1 have been imported into the bay or coastal plain and deposited since 11,700 years ago. The majority of this sediment influx is likely delivered from the east by the strong tradewind-driven littoral currents that characterize Kauai's north shore. Net carbonate sediment deposition in Hanalei Bay peaked at a rate of 15,500 m3 year−1 between 5000 and 3000 years ago (when sea level may have been 2 m above present) diminishing to 3890 m3 year−1 from 1000 years ago to the present. This influx is likely to have played a significant role in the mid to late Holocene progradation of the Hanalei shoreline.
id: 105